Psicanálise e feminismo: algumas reflexões sobre a mulher enquanto Outro - Mountian, Ilana (2020)
This article promotes a debate on otherness and gender in psychoanalysis, based on feminist theories. Feminism raises fundamental questions to psychoanalysis, requiring the revision of some of its principles - the cornerstones of its praxis - in order to expand psychoanalytical reading. While on the one hand, psychoanalysis exercises a challenging and engaged practice, on the other hand, a psychoanalytical practice without critical reflectivity may not consider the social context and the discursive effect of the position occupied by the subject. From feminist readings, psychoanalytical praxis (both theoretical and clinical) will be examined, shedding light on questions regarding gender issues, namely: the place of women (not-all/Other sex) and men (phallic) and the heteropatriarchy conjugated to it.